2016
DOI: 10.1038/srep32949
|View full text |Cite
|
Sign up to set email alerts
|

Complete Defluorination of Perfluorinated Compounds by Hydrated Electrons Generated from 3-Indole-acetic-acid in Organomodified Montmorillonite

Abstract: Here we describe a unique process that achieves complete defluorination and decomposition of perfluorinated compounds (PFCs) which comprise one of the most recalcitrant and widely distributed classes of toxic pollutant chemicals found in natural environments. Photogenerated hydrated electrons derived from 3-indole-acetic-acid within an organomodified clay induce the reductive defluorination of co-sorbed PFCs. The process proceeds to completion within a few hours under mild reaction conditions. The organomontmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 41 publications
3
86
0
Order By: Relevance
“…The hydrated electrons interact with adsorbed PFOA molecules in the interlayer of the clay. [ 136 ] PFOS UV/KI UV/KI/HA Low-pressure Hg UV light (14 W; Wavelength = 254 nm; Photon flux = 4.5 mW cm −2 ) |PFOS| = 0.02 mg/L; |KI| = 0.3 mM; |HA| = 1 mg/L pH = 10; Time = 2 h 73.9% 44.4% 0.96 h −1 Enhanced degradation of PFOS was achieved in the presence of humic acid due to the increased generation of hydrated electrons; improved electron transfer due to certain HA functionalities; absorption of UV photons by HA to produce hydrated electrons [ 137 ] 97.9% 77.0% 1.1 h −1 PFOS UV/EDTA Low-pressure Hg UV light (14 W; Wavelength = 254 nm; Photon flux = 4.5 mW cm −2 ) |PFOS| = 0.005 mg/L; |EDTA| = 2.0 mM; |HA| = 1 mg/L pH = 10; Time = 10 h 78.08% 51.19% 1.13 × 10 −1 h −1 EDTA acted primarily as OH radical scavenger. This scavenging activity allowed for the degradation of PFOS over a wide range of pH and in the presence of oxygen.…”
Section: Advanced Reduction Processes For Pfas Degradationmentioning
confidence: 99%
“…The hydrated electrons interact with adsorbed PFOA molecules in the interlayer of the clay. [ 136 ] PFOS UV/KI UV/KI/HA Low-pressure Hg UV light (14 W; Wavelength = 254 nm; Photon flux = 4.5 mW cm −2 ) |PFOS| = 0.02 mg/L; |KI| = 0.3 mM; |HA| = 1 mg/L pH = 10; Time = 2 h 73.9% 44.4% 0.96 h −1 Enhanced degradation of PFOS was achieved in the presence of humic acid due to the increased generation of hydrated electrons; improved electron transfer due to certain HA functionalities; absorption of UV photons by HA to produce hydrated electrons [ 137 ] 97.9% 77.0% 1.1 h −1 PFOS UV/EDTA Low-pressure Hg UV light (14 W; Wavelength = 254 nm; Photon flux = 4.5 mW cm −2 ) |PFOS| = 0.005 mg/L; |EDTA| = 2.0 mM; |HA| = 1 mg/L pH = 10; Time = 10 h 78.08% 51.19% 1.13 × 10 −1 h −1 EDTA acted primarily as OH radical scavenger. This scavenging activity allowed for the degradation of PFOS over a wide range of pH and in the presence of oxygen.…”
Section: Advanced Reduction Processes For Pfas Degradationmentioning
confidence: 99%
“…In contrast to oxidative processes, reduction involves the direct transformation of electrons from a reducing agent with a lower reduction potential compared to the substrate. Advanced reduction processes (ARPs), reductive metals (e.g., zero-valent iron (ZVI)), hydride radicals (H·) and most notably hydrated electrons (E 0 = −2.9 V) have been used to achieve the effective cleavage of C−F bonds in PFASs [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. The investigation of PFAS reduction reactions have shown that they are sensitive towards the choice of reagents, their concentrations and reaction times as well as pH value of the solution [ 74 , 75 , 76 ], thus can show variable efficiencies.…”
Section: State-of-the-art Liquid Reactionsmentioning
confidence: 99%
“…Under aerobic conditions, no defluorination was possible. Furthermore, a combination of 3-indole-acetic-acid and an organo-modified montmorillonite was used [ 68 ]. In this reaction, the modified clay acts as electrostatic sorbent for PFAS molecules and simultaneously it can be used as stabilizing agent for hydrated electrons originating from photo excited 3-indole-acetic acid radical cations.…”
Section: State-of-the-art Liquid Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrated electrons (e aq -) are powerful reducing agents that have been shown to be effective for degrading PFOS. Hydrated electrons can be generated using electron beam bombardment [10], gamma-ray radiation [11], and by UV photolysis of sulfite [12], iodide [13] and 3-indole acetic acid [14,15]. Electron beam and gamma-ray radiation has been used to decompose PFOS, considering the fixed cost such as high equipment cost, interest and depreciation [16], the cost is too high for an economical engineering treatment method.…”
Section: Introductionmentioning
confidence: 99%